PENDAMPINGAN LITERASI DIGITAL UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU SEKOLAH DASAR - Halimatussakdiah; Nabila , Mutiara; Harahap , Muharrina; Nurmayani; Masri Perangin-angin, Laurensia; Free Unita Manurung, Imelda (JS (JURNAL SEKOLAH), 2025)
Abstract: Improving teachers' pedagogical competence is essential to support effective and innovative learning. One of the main aspects in strengthening these competencies is digital literacy, which allows teachers to utilize technology in learning. This study aims to analyze the impact of the digital literacy mentoring program on improving the pedagogical competence of primary school teachers. The activity was conducted in Deli Tua sub-district involving 50 teachers from two elementary schools. The methods used included pre-test and post-test to measure initial understanding and skill improvement, as well as in-person and online training-based mentoring. The results showed significant improvements in the understanding and application of learning technology, with 85% of teachers understanding digital literacy and 80% able to integrate technology in learning tools. The peer-to-peer approach also proved effective in strengthening collaboration between teachers. Nonetheless, challenges such as limited access to technology and low initial skills still need to be addressed through continuous mentoring and the development of digital literacy communities. Thus, this program contributes to the transformation of digital-based education in primary schools Keyword: Digital literacy, pedagogical competence, mentoring, primary school teachers, learning technology Abstrak: Peningkatan kompetensi pedagogik guru sangat penting untuk mendukung pembelajaran yang efektif dan inovatif. Salah satu aspek utama dalam penguatan kompetensi ini adalah literasi digital, yang memungkinkan guru memanfaatkan teknologi dalam pembelajaran. Penelitian ini bertujuan untuk menganalisis dampak program pendampingan literasi digital terhadap peningkatan kompetensi pedagogik guru sekolah dasar. Kegiatan dilakukan di Kecamatan Deli Tua dengan melibatkan 50 guru dari dua sekolah dasar. Metode yang digunakan mencakup pre-test dan post-test untuk mengukur pemahaman awal dan peningkatan keterampilan, serta pendampingan berbasis pelatihan langsung dan daring. Hasil penelitian menunjukkan peningkatan signifikan dalam pemahaman dan penerapan teknologi pembelajaran, dengan 85% guru memahami literasi digital dan 80% mampu mengintegrasikan teknologi dalam perangkat pembelajaran. Pendekatan peer-to-peer juga terbukti efektif dalam memperkuat kolaborasi antar guru. Meskipun demikian, tantangan seperti keterbatasan akses teknologi dan keterampilan awal yang rendah masih perlu diatasi melalui pendampingan berkelanjutan dan pengembangan komunitas literasi digital. Dengan demikian, program ini berkontribusi terhadap transformasi pendidikan berbasis digital di sekolah dasar. Kata Kunci: Literasi digital, kompetensi pedagogik, pendampingan, guru sekolah dasar, teknologi pembelajaran